The Active Judge System in the Adversary Model: Prospects for Its Application in Indonesia - Aloysius Wisnubroto; Frisca Regina Ferreira Lay; Yohana Margareth Soumokil (International Journal of Science and Environment (IJSE), 2025)
This article examines the feasibility of adopting an active judge system within Indonesia’s adversarial model of criminal procedure. Traditionally, adversarial systems emphasize the passive role of judges as neutral arbiters between prosecution and defense, while inquisitorial systems permit judges to play an active role in fact-finding. Indonesia, rooted in the civil law tradition, has developed a hybrid legal culture that incorporates both adversarial and inquisitorial elements, particularly through its emphasis on the pursuit of material truth (kebenaran materiil). By employing a normative juridical method, this study explores whether the active judge system is compatible with Indonesia’s legal framework and constitutional guarantees of fair trial. The findings suggest that while a fully adversarial approach may not align with Indonesia’s legal tradition, a modified model that balances judicial impartiality with active engagement in fact-finding could enhance substantive justice. However, risks of bias, abuse of power, and violations of due process must be mitigated through clear procedural safeguards and judicial ethics. This article concludes that Indonesia could realistically adopt a hybrid adversarial model with inquisitorial elements, allowing for a proportionate active role of judges in ensuring justice and material truth.